Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data. (16th August 2019) - Requena Suarez, Daniela; Rozendaal, Danaë M. A.; De Sy, Veronique; Phillips, Oliver L.; Alvarez‐Dávila, Esteban; Anderson‐Teixeira, Kristina; Araujo‐Murakami, Alejandro; Arroyo, Luzmila; Baker, Timothy R.; Bongers, Frans; Brienen, Roel J. W.; Carter, Sarah; et al.
Abstract: As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1  year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1  year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1  year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research. Abstract : As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground biomass change (∆AGB) in natural forests are needed. Countries with limited forest monitoring capabilities in the (sub)tropics rely on the 2006 IPCC guidelines for default ∆AGB rates. This study provides refined default ∆AGB rate estimates based on forest plot data in younger secondary forests, older secondary forests and old‐growth forests, located in 42 countries across (sub)tropical ecozones. These new estimates contribute towards the 2019 IPCC Refinement and can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.